Process Evaluation of the Michigan Department of Corrections Residential Substance Abuse Treatment (RSAT) Program, 1999 - Austin, James ([Verlag nicht ermittelbar], 2003)
This study was a process evaluation of the Michigan Department of Corrections' (MDOC) residential substance abuse treatment (RSAT) program at the Cooper Street Correctional Facility in Jackson, Michigan. The 272-bed program was designed to treat male, minimum-custody inmates with a history of serious chemical dependency. The phase of treatment at the Jackson Cooper Street facility lasted six months, and was followed by a 12-month aftercare component. The main theory of change behind the program was that education about drugs and their physical, familial, and social effects, coupled with opportunities to learn about recovery and identify triggers for substance use, would help substance-abusing offenders to avoid both substance abuse and criminal behaviors once released into the community. This study used multiple data sources. Part 1, Michigan Department of Corrections (MDOC) Data, was acquired from the MDOC's Correctional Management Information System, which included demographic, criminal history, programming, and institutional misconduct information for a snapshot of the entire inmate population. These data provided information on all 44,061 inmates in the custody of MDOC on July 1, 1999. Part 2, RSAT Applications data, contains data for the 834 applications received by August 30, 1999. These data were received from University of Michigan (UM) researchers studying the long-term impact of the RSAT program on offender substance abuse and recidivism. The data were collected using a screening form for each application, and were initially generated and entered into an electronic format by RSAT program staff. Part 3, Service Tracking Data, contains RSAT admission and parole data, which were manually collected.